Qual técnica de análise da comunidade de fitoplanctônica (microscopia “clássica” ou metabarcoding do 16S/18S) reflete melhor as variações ambientais de um reservatório multiuso? - Hummer, Eloisa (Universidade Federal de São Carlos, 2025)
Phytoplankton, composed of photosynthetic prokaryotic and eukaryotic microorganisms, play fundamental roles in biogeochemical cycles and form the base of aquatic food webs. Because phytoplankton responds rapidly to environmental shifts, they serve as effective indicators of water quality. Comparative studies have shown that phytoplankton community analyses based on morphological identification under an inverted optical microscope (the “classical” method) or on metabarcoding of 18S amplicons (targeting eukaryotes) and 16S amplicons (targeting prokaryotes such as cyanobacteria, but also chloroplasts of autotrophic eukaryotes) can both be applied for aquatic ecosystem monitoring. However, different methods likely depict the environment in distinct ways, and determining which approach is most suitable for assessing aquatic environmental dynamics remains a challenge. In this study, microscopy and sequencing data were obtained from 60 samples collected monthly by the Broa/Lobo Reservoir Microbial Observatory (BroaMO). Community composition dynamics were examined and related to environmental variables using multivariate analyses. The three methods were compared to evaluate which one best captures the dynamics of the aquatic environment and water quality. The central hypothesis is that each method provides different insights into species composition and abundance. Although molecular approaches offer higher resolution regarding community abundance patterns and temporal dynamics, microscopy proved more effective in describing environmental conditions and explaining environmental variability. Thus, we conclude that each approach portrays the environment differently within its methodological limitations, and that integrating traditional and molecular methods can enhance community analyses by providing a broader and more accurate understanding of phytoplankton dynamics and their responses to environmental change.
Which phytoplankton community analysis approach (classical microscopy or 16S/18S metabarcoding) better captures environmental variability in a multipurpose reservoir?
Keywords: Amplicons; Microscopia; Monitoramento ambiental; Águas continentais; Qualidade da água; Bioindicadores; Amplicon sequencing; Metabarcoding; Microscopy; Environmental monitoring; Freshwater systems; Water quality; Bioindicators; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA DE ECOSSISTEMAS; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA DE ECOSSISTEMAS; CIENCIAS BIOLOGICAS; 14. Vida na Água